2016
DOI: 10.1186/s12889-016-3007-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with secondhand smoke exposure in different settings: Results from the German Health Update (GEDA) 2012

Abstract: BackgroundThe ubiquity of secondhand smoke (SHS) exposure at home or in private establishments, workplaces and public areas poses several challenges for the reduction of SHS exposure. This study aimed to describe the prevalence of SHS exposure in Germany and key factors associated with exposure. Results were also differentiated by place of exposure.MethodsA secondary data analysis based on the public use file of the German Health Update 2012 was conducted (n = 13,933). Only non-smokers were included in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
(31 reference statements)
6
18
0
2
Order By: Relevance
“…The Dutch study reported that workers who were male and low-educated were more likely to be exposed to SHS [8]. The German study reported the aspect of higher SHS exposure in younger age group, but this is dependent on the place of exposure, and exceptionally at workplace, 30–44 years had highest SHS exposure differ by the others such as home, bars, or the house of friend [9]. It is known that blue-collar workers and service workers are more likely to expose the higher rate of SHS occupationally than white-collar workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch study reported that workers who were male and low-educated were more likely to be exposed to SHS [8]. The German study reported the aspect of higher SHS exposure in younger age group, but this is dependent on the place of exposure, and exceptionally at workplace, 30–44 years had highest SHS exposure differ by the others such as home, bars, or the house of friend [9]. It is known that blue-collar workers and service workers are more likely to expose the higher rate of SHS occupationally than white-collar workers.…”
Section: Discussionmentioning
confidence: 99%
“…Working adults spend most of their time at workplace and for those non-smokers, the workplace may be the major source of provider to SHS exposure [8]. In the German study, More than 40% of non-smokers reported experiencing SHS at work [9]. Workplace smoking is an occupational health hazard and a smoking ban policy at the workplace is the best option to reduce SHS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also highlighted the higher likelihoods of ETS exposure at home for socioeconomically-disadvantaged people [46,47,48,49]. The present study has documented that, even though the smoking prevalence among social aid recipients tends to be higher [43], the prevalence of ETS exposure for the population of the Piotrkowski District was found to be much lower than in the general population, where 15.5% of the non-smokers (6.6% of males and 18.3% of females, respectively) were exposed to ETS in the month preceding the study.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, esta investigación encontró que las mujeres, los adolescentes y los grupos de menor nivel educativo tienen una mayor exposición al HTSM en el hogar. Estos resultados son consistentes con la mayoría de los estudios a nivel mundial, [23][24][25][26][27][28][29][30][31][32] lo que muestra que las inequidades de género, edad y nivel educativo persisten en nuestro país y afectan principalmente en el hogar, donde 10 millones de mexicanos continúan expuestos al HTSM. En los hombres, la exposición es mayor en los espacios públicos y de trabajo.…”
Section: Resultsunclassified
“…Este hallazgo se reporta en estudios previos en la literatura internacional. [27][28][29][30][31] Finalmente, vivir en áreas urbanas o metropolitanas se asocia con una mayor exposición al HTSM en todos los lugares. Lo anterior contrasta con lo encontrado en algunos países, donde la mayor exposición en el trabajo y en el hogar se observa en las áreas rurales.…”
Section: Resultsunclassified